Answer: D. [tex]a_n=6+(n-1)(-3)[/tex]
Step-by-step explanation:
Given : An arithmetic sequence has this recursive formula:
[tex]a_1=6 \ \ \; \ a_n=a_{n-1}-3[/tex]
Using the given information, Second term of arithmetic sequence will be :-
[tex]a_2=a_{1}-3=6-3=3[/tex]
That means common difference = [tex]a_2-a_1=3-6=-3[/tex]
The explicit formula for arithmetic sequence is given by :-
[tex]a_n=a+(n-1)d[/tex], where a is the first term and d is the common difference.
Put a= 6 and d= -3, we get
The explicit formula for this sequence :-
[tex]a_n=6+(n-1)(-3)[/tex]